Mesenteric inflammatory pseudotumor: A difficult diagnosis. Case report. (2017) - Lopes, Vítor Neves; Alvarez, César; Dantas, M. Jesus; Freitas, Carla; Pinto-de-Sousa, João
Highlights: Inflammatory pseudotumor is a very rare benign neoplasm. Definitive diagnosis is usually made only after surgery. Mesenteric location is rare. Surgical resection can cure the disease. Close follow-up is advised to identify recurrences. Abstract: Introduction: Inflammatory pseudotumor (IP) is an uncommon benign neoplasm. It was first described in the lung but it has been recognized in several somatic and visceral locations. Mesenteric presentation is rare and its clinical presentation is variable but patients can be completely asymptomatic. Complete surgical resection is the only curable treatment. Rational follow-up protocols have not been established yet. Presentation of case: A 57 years-old man, with no relevant comorbidities and completely asymptomatic, apart from a lump on the right hypochondrium, was submitted to surgical resection of a large mesenteric mass. The preoperative Computed Tomography suggested gastrointestinal stromal tumor as the most probable diagnosis. Definitive histological examination of the completely resected surgical specimen confirmed the diagnosis of IP. The patient has been on follow-up for four years, without no evidence of recurrence. Discussion: The preoperative diagnosis of IP may be difficult to establish mainly due to the lack of a typical clinical presentation. It is a rare entity, particularly in the adult population. These two aspects make it easier to neglect this entity in the differential diagnosis of an abdominal mass on asymptomatic adults. Although there are no formal guidelines on follow-up, close follow-up seems to be advisable in these patients as recurrence is frequent. Conclusion: IP should be present as a possible differential diagnosis in an abdominal mass. Complete excision of the lesion can be curable but close follow-up seems to be required.